The role of magnetic resonance imaging technique in detection dentofacial pattern among Diyala Governorate population - Hakiem Tawfieq , Ali (Diyala Journal of Medicine, 2023)
Background: Magnetic Resonance Imaging is accepted as the most advanced imaging modality for diagnosis of maxillofacial soft tissue abnormalities. It is noninvasive and has the potential to yield high quality tomographic imaging in any plane with bone as well as soft tissue spatial resolution. Additionally, the patient is not exposed to ionizing radiation or any biological hazards. Objective: To determine the depth of masseter muscle in various vertical dentofacial shapes and to relate masseter muscle depth with craniofacial shapes using magnetic resonance imaging technique (MRI). Patients and Methods: Thirty youthful, healthy people overall between the ages of 16 and 40 were chosen and divided into three groups of ten, using (MRI), categorize each as a vertical, average, and horizontal grower. The concepts masseter muscles had their different anatomical dimensions sagittal, axial, and coronal directions utilizing MRI perspectives. Results: Our study found the difference is significant when comparing between the growth patterns in both direction (horizontal and vertical)(p<0.05), also the direction of muscle fibers of masseter muscle (anterior and posterior) away from first molar to the zygomatic arch was saved. In contrast to the horizontal list, when the fibers are attached anteriorly and vertically at the jaw angle, we discovered in our research that the direction of the muscle fibers is toward the posterior side more than anterior side and at a sharper angle. Conclusion: The study found that the muscle fibers in the extra posterior direction had a steeper angle than the horizontal group, with the vertical fiber orientation having an anterior connection at the angle of the mouth.